Field assessment of potential exposure of dogs to leptospirosis by measuring antibody titers in dogs: a multisite study in five geographic regions of the United States - Carithers, Doug; Loebach, Ed; Williams, Troy; Sponseller, Jerlyn; Schreibman, Andrew; Platts, Diane (Frontiers in Veterinary Science, 2024)
Leptospirosis vaccine for dogs in the United States is considered a lifestyle or non-core vaccine, making individual veterinary practitioners responsible for determining if vaccination is necessary for their patients. Veterinary professionals often base their vaccination decisions on local rates of clinical cases. However, even subclinical leptospirosis infections have zoonotic potential. The microscopic agglutination test (MAT) is effective for screening unvaccinated animals, but previous vaccination can lead to inconsistent results and variable MAT titers over time. This prospective research survey evaluated if local experience was sufficient to justify selective vaccination for leptospirosis. MAT analyses were performed on sera collected from well-cared-for, unvaccinated dogs residing in five different geographies across the United States: South-Central (East Texas), New England, the Mid-Atlantic (North Carolina and Virginia), Midwest (Wisconsin/northern Illinois), and Southwest (southern California). Thirty-eight clinics participated, submitting a total of 1345 qualified samples from unvaccinated dogs over 1 year of age. 11.6% of these unvaccinated dogs had MAT titers for one or more serogroups of Leptospira. While seropositivity does not necessarily indicate that disease will result or that a specific serovar is involved, these MAT-positive cases do indicate that the potential for exposure exists and clinical signs or a carrier-state could result from infection. These survey results would indicate that a more aggressive vaccination protocol for leptospirosis should be considered.